Analyzing the effect of organic carbon on partial nitrification‐anammox process based on metagenomics and quorum sensing. (1st August 2020) - Xing, Lizhen; Liu, Minglei; Zhang, Yanhao; Zhang, Weikang; Wang, Zifan
Abstract: The effects of adding organic carbon on the performance of different partial nitrification‐anammox (PNA) process (the activated sludge process and biofilm process) were studied, especially nitrogen removal, functional microbial activity, and microbial community structure. The potential influences of quorum sensing (QS) on the nitrogen metabolism were also analyzed. The results showed that the addition of organic carbon in biofilm systems could reduce total nitrogen (TN) removal percentages, while in activated systems it could increase TN removal percentages. The TN removal percentages in SBBR‐CN (the biofilm system with addition of organic carbon) and SBR‐CN (the activated sludge system with addition of organic carbon) were 15% and 45%, respectively, and those in SBBR‐N (the biofilm system without addition of organic carbon) and SBR‐N (the activated sludge system without addition of organic carbon) were 75% and 21%, respectively. Batch experiments have proved that organic carbon inhibited the activities of nitrite‐oxidizing bacteria (NOB) and anaerobic ammonia oxidation (anammox) bacteria, and organic carbon could promote the activity of denitrifying bacteria in activated sludge systems. Compared with activated sludge systems, biofilm systems could protect the activity of anammox bacteria. The relative abundances of ammonia oxidizing bacteria (AOB) and anammox bacteria were decreased, while the relative abundances of denitrifying bacteria ( Thauera ) were increased with the addition of organic carbon. The biofilm systems were more conducive to the growth of anammox bacteria. Metagenomics revealed that the same bacteria might be involved in different nitrogen metabolism, and nitrogen metabolism was achieved through the complex cooperation among functional bacteria. Besides, functional bacteria involving in the nitrogen metabolism had genes related to QS, indicating that QS might affect the nitrogen metabolism by regulating the functional bacteria activity. Practitioner points: PNA was achieved through SBBR and complete nitrification was achieved through SBR under the low ammonia nitrogen concentration condition. The effect of organic carbon on biofilm and activated sludge PNA process was different under the low ammonia nitrogen concentration condition. QS and QQ may affect the nitrogen removal performance by regulating the expression of nitrogen metabolism‐related genes. Abstract : The difference of TN removal percentages and microbial community structure in SBBRs and SBRs.